Avaliação bidimensional do transporte do canal radicular após diferentes técnicas de instrumentação mecanizada - Tameirão, Michele Dias Nunes (2014)
The purpose of this study was to compare the ability of Reciproc, TF Adaptive and WaveOne systems in maintaining the root canal anatomy. ProTaper Universal system was used as reference for comparison. Forty (40) simulated curved root canals in clear resin blocks were randomly assigned to 4 groups (n=10) accordingly to the instrumentation system: Reciproc (VDW, Munich, Germany), TF Adaptive (SybronEndod, California, USA) WaveOne (Dentsply Maillefer, Ballaigues, Switzerland) and ProTaper Universal (Dentsply Maillefer) groups. Color stereomicroscopic images from each block were taken before and after instrumentation. All image processing and data analysis were performed with an open source program (FIJI). Evaluation of canal transportation was obtained for the whole canal and for two independent regions: straight part and curvature portion. The results showed that all tested system caused canal transportation. In the straight part, ProTaper Universal caused more transportation then the other tested systems (P<0.05). No differences were observed in the straight part when comparing TF Adaptive, Reciproc and WaveOne. TF Adaptive caused significantly less canal transportation in the curvature portion than Reciproc, WaveOne and ProTaper Universal systems (P<0.05). ProTaper Universal system caused more transportation than the other tested systems in the straight part and in the curvature portion (P<0.05). Within the limitations of this study, it can be concluded that TF Adaptive produced overall less canal transportation when compared with the others tested systems. The multi-file rotary system ProTaper Universal caused more canal transportation then the other tested systems.